2022
DOI: 10.1101/2022.06.14.496108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of Storage Condition and Duration on Function of Native and Cargo-Loaded Mesenchymal Stromal Cell Extracellular Vesicles

Abstract: As evidenced by ongoing clinical trials and increased activity in the commercial sector, extracellular vesicle (EV)-based therapies have begun the transition from bench to bedside. As this progression continues, one critical aspect to EV clinical translation is understanding the effects of storage and transport conditions. Several studies have assessed the impact of storage on EV characteristics such as morphology, uptake, and component content, but effects of storage duration and temperature on EV functional … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…HUVECs were used to evaluate effects on endothelial tube formation as previously described [30]. In brief, HUVECs were trypsinized, counted, and aliquoted into a tube marked 13 for each treatment that was filled with 2 mL of EBM2 supplemented with 0.1% FBS and 1% P/S.…”
Section: Tube Formation Assaymentioning
confidence: 99%
“…HUVECs were used to evaluate effects on endothelial tube formation as previously described [30]. In brief, HUVECs were trypsinized, counted, and aliquoted into a tube marked 13 for each treatment that was filled with 2 mL of EBM2 supplemented with 0.1% FBS and 1% P/S.…”
Section: Tube Formation Assaymentioning
confidence: 99%
“…20,22,28,29 Various authors investigated the effect of the freeze-drying process on EVs from various sources, and as previously described for cryopreservation, they observed that the stability of lyophilized EVs depends on their origin. 28−30 Besides that different researchers freeze-dried EVs without additives, 29,31,32 in general, to successfully maintain the original vesicles' features, lyophilization of EVs from different sources requires the addition of cryo-and lyoprotectants to preserve them during the process. One of the most widely used protecting agents for freeze-drying is trehalose; lyophilized EVs with trehalose, alone or in combination with other compounds, such as poly(vinylpyrrolidone) 40, 33 were similar to the ones stored at −80 °C in terms of size, morphology, concentration, and content of proteins and RNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Various authors investigated the effect of the freeze-drying process on EVs from various sources, and as previously described for cryopreservation, they observed that the stability of lyophilized EVs depends on their origin. Besides that different researchers freeze-dried EVs without additives, ,, in general, to successfully maintain the original vesicles’ features, lyophilization of EVs from different sources requires the addition of cryo- and lyoprotectants to preserve them during the process. One of the most widely used protecting agents for freeze-drying is trehalose; lyophilized EVs with trehalose, alone or in combination with other compounds, such as poly­(vinylpyrrolidone) 40, were similar to the ones stored at −80 °C in terms of size, morphology, concentration, and content of proteins and RNAs. ,, The addition of sucrose to the EVs formulation before freeze-drying allowed the maintenance of their original features after the rehydration. , Mannitol showed fewer promising results than trehalose and sucrose for the maintenance of the original EVs’ concentration and morphology upon lyophilization. , In contrast, poly­(ethylene glycol) (PEG) did not demonstrate good stabilization behavior for EVs, since it induced the aggregation of particles, probably by crosslinking the vesicles …”
Section: Introductionmentioning
confidence: 99%
“…Extracellular vesicles (EVs), specifically those from mesenchymal stem cells (MSCs), have emerged as an intriguing therapeutic alternative to whole-cell therapies in a multitude of applications (e.g., sepsis, cancer, wound healing) with additional promise as efficient drug delivery vehicles [1, 2]. With an improved safety profile [3], favorable storage requirements [4], and the ability to traverse biological barriers [5, 6], MSC EVs represent a promising and effective alternative to their parental cells. However, there exist fundamental obstacles that hinder the translation of MSC EVs, including a lack of a rationally designed production platform and low therapeutic potency (i.e., low levels of endogenous EV cargos).…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular vesicles (EVs), specifically those from mesenchymal stem cells (MSCs), have emerged as an intriguing therapeutic alternative to whole-cell therapies in a multitude of applications (e.g., sepsis, cancer, wound healing) with additional promise as efficient drug delivery vehicles [1,2]. With an improved safety profile [3], favorable storage requirements [4],…”
Section: Introductionmentioning
confidence: 99%